Documenting death : maternal mortality and the ethics of care in Tanzania - Strong, Adrienne E., 1988- (University of California Press, 2020)
"Documenting Death is a gripping ethnographic account of the deaths of pregnant women in a hospital in a low-resource setting in Tanzania. Through an exploration of everyday ethics and care practices on a local maternity ward, anthropologist Adrienne E. Strong untangles the reasons Tanzania has achieved so little sustainable success in reducing maternal mortality rates, despite global development support. Growing administrative pressures to document good care serve to preclude good care in practice while placing frontline healthcare workers in moral and ethical peril. Maternal health emergencies expose the precarity of hospital social relations and accountability systems, which, together, continue to lead to the deaths of pregnant women"--